The Making of Cereal With Subtitution of Soybean Flour (Glycine Max L. Merr) and Pasta Fruit Bit (Beta Vulgaris L) As Natural Dyes - Hirwan Amanda; Irmayanti Irmayanti; Rita Sunartaty (Serambi Journal of Agricultural Technology, 2021)
Making cereals using wheat flour is a problem because the raw materials obtained are more expensive. In addition, wheat flour will have an adverse effect on some people who are sensitive to gluten. One of the best alternatives to wheat flour in the manufacture of cereals to produce low-gluten cereal products is tapioca flour. The purpose of this study is to determine the effect of adding soybean flour, beetroot paste and its interaction on physical and organoleptic characteristics of cereals. The results showed that the best treatment was found in the addition of 60% soybean flour and 85% beetroot paste (K3B3) which produced good quality serela with chemical properties, namely water content of 4.67%, yield 63.00%, water absorption 13, 10%, crispiness in milk 106 seconds, organoleptic test for taste 3.94 (like), aroma 4.10 (like), texture 2.67 (ordinary) and color 3.83 (like).